Myocardial oxidative stress is increased in early reperfusion, but systemic antioxidative therapy does not prevent ischemia-reperfusion arrhythmias in pigs - Haugsten Hansen, Marie; Sadredini, Mani; Hasic, Almira; Eriksen, Morten; Stokke, Mathis Korseberg (Frontiers in Cardiovascular Medicine, 2023)
Background Arrhythmias in the early phase of reperfusion after myocardial infarction (MI) are common, and can lead to hemodynamic instability or even cardiac arrest. Reactive oxygen species (ROS) are thought to play a key role in the underlying mechanisms, but evidence from large animal models is scarce, and effects of systemic antioxidative treatment remain contentious. Methods MI was induced in 7 male and 7 female pigs (Norwegian landrace, 35–40 kg) by clamping of the left anterior descending artery (LAD) during open thorax surgery. Ischemia was maintained for 90 min, before observation for 1 h after reperfusion. Pigs were randomized 1:1 in an operator-blinded fashion to receive either i.v. N-acetylcysteine (NAC) from 70 min of ischemia and onwards, or 0.9% NaCl as a control. Blood samples and tissue biopsies were collected at baseline, 60 min of ischemia, and 5 and 60 min of reperfusion. ECG and invasive blood pressure were monitored throughout. Results The protocol was completed in 11 pigs. Oxidative stress, as indicated by immunoblotting for Malondialdehyde in myocardial biopsies, was increased at 5 min of reperfusion compared to baseline, but not at 60 min of reperfusion, and not reduced with NAC. We found no significant differences in circulating biomarkers of myocardial necrosis, nor in the incidence of idioventricular rhythm (IVR), non-sustained ventricular tachycardia (NSVT), ventricular tachycardia (VT) or ventricular fibrillation (VF) between NAC-treated and control pigs during reperfusion. Conclusion Myocardial oxidation was increased early after reperfusion in a porcine model of MI, but systemic antioxidative treatment did not protect against reperfusion arrhythmias.